When Believing in Divine Immanence Explains Vaccine Hesitancy: A Matter of Conspiracy Beliefs? - Ladini, Riccardo (2022)
This article analyzes the relationship between religiosity and vaccine hesitancy by highlighting the role of a specific dimension of religiosity that makes some people more prone to explaining health conditions as a divine agency—the belief in the immanent presence of the divine in everyday life. Accordingly, these people may undervalue the role of vaccination as a solution to cope with a pandemic and may be more skeptical of vaccines. We suggest a mechanism explaining the relationship between religiosity and vaccine hesitancy by focusing on the mediating role of beliefs in conspiracy theories, given that belief in divine immanence and conspiracy theories share the common trait of attributing agency to hidden forces. Beliefs in conspiracy theories, in turn, have been shown to be among the strongest predictors of vaccine hesitancy. By using a moderated mediation analysis on Italian survey data collected during the Covid-19 pandemic, we show that such a mechanism helps explain the relationship between believing in divine immanence and vaccine hesitancy among people not adhering to institutional religiosity. In contrast, this mechanism does not apply when the immanent conception of the divine is framed within a system of beliefs belonging to institutional religion.